United States, family eating meal at home in Utqiaġvik - Sorensen, Clarence Woodrow, 1907-1982; Harris, Eugene V., 1913-1978 (1959)
Mother helping feed child sitting next to her at meal. Grayscale Sorensen Safety Negatives, Binder: North & Central America 3